Multiple metachronous and synchronous malignancies with lung and thorax involvement. Report of two cases - Sapalidis, Konstantinos; Schizas, Nikos; Lazopoulos, Achileas; Kamparoudi, Parthena; Paliouras, Dimitris; Sardeli, Chrysa; Konstantinou, Fotis; Chatzinikolaou, Fotis; Sarafis, Pavlos; Zarogoulidis, Paul; Kougioumtzi, Ioanna; Katsikogiannis, Nikolaos; et al. (My University, 2018)
Multiple primary malignant neoplasms (MPMN) is an uncommon phenomenon, while the diagnosis of such conditions is very significant. Considering that the strategy of the treatment is determined by the histological type of the tumor, practitioners should be alert in order to avoid malpractices in cases of multiple metachronous or synchronous malignancies. In this article we report two rare cases of MPMN. The first patient suffered from three metachronous malignant neoplasms, specifically tonsillar, lung and breast cancer, while the second patient was diagnosed with four synchronous and metachronous malignant tumors, including renal and lung cancer, basaloid carcinoma and melanoma. Such cases are extremely rare in the clinical practice and poorly described in the literature.
Keywords: Basaloid carcinoma; Lung cancer; Malignant neoplasms; Metachronous; Multiple